1992
DOI: 10.1002/mrd.1080330416
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between in vitro fertilization and microinjection of immobilized spermatozoa from bulls producing spermatozoa with defects

Abstract: The objectives of this study were to compare the fertilization rate of bovine in vitro matured oocytes by in vitro fertilization (IVF) and by microinjection of a single spermatozoon (MI) and to relate these rates with fertility reported for these bulls in artificial breeding. Bull A (Holstein) had a nonreturn rate of 75%. Semen from this bull is routinely used in our standard IVF procedure. Bull B (Ayrshire), used regularly in artificial breeding and related to bull D, had a nonreturn rate of 69.2%. Bull C (Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The reason for the variability, however, is still unknown. Heuwieser et al (1992a) used sperm from infertile bulls for ICSI with in vitro matured bovine oocytes and achieved fertilization rates comparable to those with sperm from bulls proven to be fertile by IVF. This indicates that the fertilizability of sperm in ICSI is not coincident with their performance in IVF.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the variability, however, is still unknown. Heuwieser et al (1992a) used sperm from infertile bulls for ICSI with in vitro matured bovine oocytes and achieved fertilization rates comparable to those with sperm from bulls proven to be fertile by IVF. This indicates that the fertilizability of sperm in ICSI is not coincident with their performance in IVF.…”
Section: Discussionmentioning
confidence: 99%
“…The sterile bull with 100% ter-atospermia in the present study appears to exhibit the effects of an autosomal recessive gene transmitted through heterozygous males and females . Heuwieser et al (1992) reported that bull sperm exhibiting similar teratospermia and sperm with normal morphology produced by a subfertile bull with a transmissable chromosomal anomaly (Kovács et al, 1992) could fertilize few oocytes in an IVF system, but this was increased by microinjection. Lonergan et al (1994) reported that sperm from a subfertile bull carrying a 1/29 chromosomal translocation fertilized fewer bovine oocytes than sperm from a control bull.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Its advantages make it the method of choice for very delicate operations such as nuclear transfer in the context of generation of transgenic animals. [11] Microinjection would likely be the method of choice for intracellular delivery of macromolecules if its main disadvantages of being slow and expensive were eliminated. Efforts to reduce the cost and increase throughput include automated microinjection devices based on robotic systems[12] and microfluidic systems that move cells onto fixed microneedles.…”
Section: Introductionmentioning
confidence: 99%